2016
DOI: 10.1177/0954407016656290
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the folding rear-seat aperture in the acoustic response of a sedan car

Abstract: The coupled vibro-acoustic response of a sedan is analysed, and the effect of the folding rear-seat aperture is studied. First, a simplified model of an acoustic cavity that consists of two adjacent boxes connected by an aperture is modelled. An analytical solution is proposed to calculate the acoustic eigenfrequencies of the simplified model. Then, the uncoupled acoustic eigenfrequencies of the actual cavity (where the trunk cavity and the cabin cavity are connected through an aperture) are computed. It is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Regarding the general framework of vibro-acoustic studies, it is known that in It is assumed that the eigenfrequencies of the actual cavity can be calculated approximately using its simplified geometry. It is shown that this assumption holds in the low frequency bandwidth, namely below 250 Hz (Xu et al, 2014;Oktav et al, 2016).…”
Section: Simplified Geometrymentioning
confidence: 97%
“…Regarding the general framework of vibro-acoustic studies, it is known that in It is assumed that the eigenfrequencies of the actual cavity can be calculated approximately using its simplified geometry. It is shown that this assumption holds in the low frequency bandwidth, namely below 250 Hz (Xu et al, 2014;Oktav et al, 2016).…”
Section: Simplified Geometrymentioning
confidence: 97%
“…He suggested creating a slit between the boot and the passenger cabin. A few other researchers have also studied the installation of Helmholtz resonators to minimize cabin noise in automobiles [32][33][34][35][36]. Apart from automobile cabins, the Helmholtz resonator has also been used to minimize aircraft cabin noises.…”
Section: Helmholtz Resonatormentioning
confidence: 99%
“…Much of this work has been focused on vehicle body. e internal sound field in the enclosed cavity is shown to be significantly affected by the acoustic characteristics of the cavity, the structural vibration of the compartment wall panels and the coupling of these two dynamic systems [8][9][10][11][12][13][14][15][16][17]. Since the amount of absorptive material required to control lowfrequency noise can be prohibitively large, the most practical solution to the problem would seem to be modification of the vehicle structure.…”
Section: Introductionmentioning
confidence: 99%